Isolation of aFlavonoid Bioactive compound fromGymnoascus dankaliensis Secondary Metabolite - Jafar, Furdos Noori; Sabah, Fatima S. (Iraqi Journal of Science, 2024)
Flavonoids, a wide range of phenolic compounds produced as secondary metabolites in plants, bacteria and fungi, have highly potent activities. In this study, the fungus  Gymnoascus dankaliensis was isolated in spring from sheep dung samples, and itsability to produce a secondary metabolite was investigated. The fungal secondary metabolite was extracted, and the antimicrobial and antioxidant activitis were tested. The results showed that Gymnoascusdankaliensis, thefirst ever isolated fungus from dung in Basrah, could produce a secondary metabolite that were produced using a Solid State Ferementation SSF medium after 40 days of incubation. The bioactive compounds were extracted from the solid media by using ethyl acetate. The chemical identification of the extracted bioactive compound indicated that the isolated compound belonged to the flavonoid group. The isolated flavonoid compound tested as an antimicrobial agent against three clinical isolates of bacteria,Escherichia coli , Staphylococcus aureus and  and Bacillus subtilis, was also tested against two yeast isolates Candida albicans and C. tropicalis. The results recorded the largest inhibition zone in S.aureus. Whereas C.albicans was found to be more sensitive toward the isolated flavonoid compound than C. tropicalis. The antioxidant activity of the isolated compound was investigated using DPPH (1,1-diphenyl-2-picrylhydrazyl) method where it showed moderate antioxidant  activity compared to ascorbic acid.